Der Steinkohlenbergbau in Boom und Krise nach 1945 Transformationsprozesse in der Schwerindustrie am Beispiel des Ruhrgebiets - Bluma, Lars / Czierpka (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2021)
This volume presents the papers from the conference Coal Mining in Boom and Crisis since 1945: The Ruhr Region as a Comparative Template for Processes of Transformation in Heavy Industry held at the German Mining Museum Bochum in March 2017, inquiring into the suitability of the Ruhr mining industry that dominates the region as a comparative template for processes of transformation in heavy industry.